2007
DOI: 10.1055/s-2007-962947
|View full text |Cite
|
Sign up to set email alerts
|

Klinische Befunde eines Patienten mit Lowe-Syndrom und einer Splice Site Mutation im OCRL1-Gen

Abstract: The oculo-cerebro-renal syndrome of Lowe (OCRL) is a rare X-chromosomal disorder characterised by the triad of congenital cataracts, renal tubular dysfunction, and mental retardation. Typically complete opacification and discoid deformation of the lenses are seen, indicating a developmental defect in early embryogenesis. We report on a 35-year-old patient with a mild Lowe syndrome phenotype including incomplete lenticular opacities. Clinical findings suggest that the gene product of the mutated allele (IVS19 +… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Hichri et al [22] reported two mutations (p.Ile274Thr, p.Arg318Cys) that have been associated with mild Lowe syndrome (Dent-2 disease) [8,9,12,55,56] but can also cause the severe phenotype even within the same family. A premature termination mutation (p.Gln199X) and a splice variant (IVS19+1G>A) were found to be associated with Lowe syndrome at patient's ages of 13 yr and 29 yr, respectively [10,57]. Both these cases had remained undiagnosed due to absence of congenital cataract or even any ocular involvement [10,57].…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
See 2 more Smart Citations
“…Hichri et al [22] reported two mutations (p.Ile274Thr, p.Arg318Cys) that have been associated with mild Lowe syndrome (Dent-2 disease) [8,9,12,55,56] but can also cause the severe phenotype even within the same family. A premature termination mutation (p.Gln199X) and a splice variant (IVS19+1G>A) were found to be associated with Lowe syndrome at patient's ages of 13 yr and 29 yr, respectively [10,57]. Both these cases had remained undiagnosed due to absence of congenital cataract or even any ocular involvement [10,57].…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
“…A premature termination mutation (p.Gln199X) and a splice variant (IVS19+1G>A) were found to be associated with Lowe syndrome at patient's ages of 13 yr and 29 yr, respectively [10,57]. Both these cases had remained undiagnosed due to absence of congenital cataract or even any ocular involvement [10,57]. On the other hand, only minimal signs of tubular dysfunction and a mild behavioral and cognitive phenotype were found in association with an OCRL p.Glu851X nonsense mutation and a mild renal phenotype was also described due to an c.1244+5G>A defect [58,59].…”
Section: Genotype-phenotype Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically complete opacification and discoid deformation of the lenses (microphakia) are seen, indicating a developmental defect in early embryogenesis ( Figure 2). Patients with mild Lowe syndrome phenotype may show incomplete lenticular opacities without visual impairment [6].…”
Section: Journal Of Genetic Syndromes and Gene Therapymentioning
confidence: 99%